If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y + z = -1 Solving 2x + -1y + z = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -1y + y + z = -1 + y Combine like terms: -1y + y = 0 2x + 0 + z = -1 + y 2x + z = -1 + y Add '-1z' to each side of the equation. 2x + z + -1z = -1 + y + -1z Combine like terms: z + -1z = 0 2x + 0 = -1 + y + -1z 2x = -1 + y + -1z Divide each side by '2'. x = -0.5 + 0.5y + -0.5z Simplifying x = -0.5 + 0.5y + -0.5z
| 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= | | (-3b^2-7b-4)+(7b^2+2b-4)= | | 4t+5+4t-7t=6+2 | | x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) | | 8m+m=14+5m | | 7x+6x-4x=16+2 | | 2(m-3)=2(m-2.5) | | 30*50=x | | 30x*50=x | | 51-x=36 | | 14k(8-k+h)= | | 40c+120a=500 | | 5m-2=4+m | | -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 | | -9x-101-3x=79 | | 8x^2y+-5yx^2= | | 0.02x=5 |